2018
DOI: 10.1021/acsbiomaterials.8b00060
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Laser Interference Lithography to Make Nanopatterned Surfaces for Fundamental Studies on Stem Cell Response

Abstract: The extracellular matrix (ECM) is a nanostructured environment that provides chemical, mechanical, and topographical stimuli for various cellular functions. Here, we introduce the application of laser interference lithography (LIL) to generate hexagonally arranged gold nanostructures of three different dimensions on silicon to study the effect of feature dimensions on human adipose-derived stem cells (hADSC) in terms of adhesion, growth, and differentiation. Self-assembled monolayers (SAM) were used to passiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 70 publications
0
29
2
Order By: Relevance
“…35,36 In previous studies we could show that LIL can be used to design defect-free structures of gold of different size and periodicity on silicon as model surface. 24 We could demonstrate further that spreading of human adipose-derived stem cells (hADSC) decreased with increasing feature dimensions, which had an effect on cell differentiation. 24 In another study we studied how polyelectrolyte multilayers (PEM) made of hyaluronic acid (HA) and poly-L-lysine (PLL), either as native or cross-linked system varying in elastic modulus, guide hADSC adhesion, growth, and differentiation.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…35,36 In previous studies we could show that LIL can be used to design defect-free structures of gold of different size and periodicity on silicon as model surface. 24 We could demonstrate further that spreading of human adipose-derived stem cells (hADSC) decreased with increasing feature dimensions, which had an effect on cell differentiation. 24 In another study we studied how polyelectrolyte multilayers (PEM) made of hyaluronic acid (HA) and poly-L-lysine (PLL), either as native or cross-linked system varying in elastic modulus, guide hADSC adhesion, growth, and differentiation.…”
Section: Introductionmentioning
confidence: 84%
“…24 We could demonstrate further that spreading of human adipose-derived stem cells (hADSC) decreased with increasing feature dimensions, which had an effect on cell differentiation. 24 In another study we studied how polyelectrolyte multilayers (PEM) made of hyaluronic acid (HA) and poly-L-lysine (PLL), either as native or cross-linked system varying in elastic modulus, guide hADSC adhesion, growth, and differentiation. 37 We found that hADSC spread and grew more on stiffer, highly cross-linked than on soft native PLL/HA multilayers.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations